PERANAN WORLD WIDE FUND FOR NATURE (WWF) DALAM KONSERVASI TAMAN NASIONAL TESSO NILO (TNTN) - Eva Yeni Hutabalian; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes the land and forest fires that have large impact on a varioussectors, such as the economy, transportation, agricultural production, the level of publichealth and state relations. Tesso Nilo National Park area suffered damage alarming variousparties, including the Non-Government Organizations (NGO) and International GovernmentOrganizations (IGOs). The state of Tesso Nilo National Park has changed completely as aresult of the increase in economic activity of the local population. This environmental issue isnot just domestic problem of Riau administration or Indonesian government, but also beinginternational community concern.To analyze the research question, the writer uses constructivism. Constructivismassumes that shared ideas and values form the identity (ideational identity), which in turnaffects interest. Ideational identity and interests is what ultimately helped determine politicalaction. Constructivism gives attention to the importance and existing public discourse insociety because discourse reflects and form beliefs and interests, and maintain norms thatunderlie the community acted.This research shows WWF role in the establishment of conservation areas Tesso NiloNational Park, beginning with cooperation with stakeholders including BKSDA Riau, Riauprovincial government in this case the Riau Provincial Forestry Office, District Governmentin this case the District Forestry Office Riau province, local people and various companiesthat operating in related areas.Keyword: conservation, degradation, illegal logging, Non-Governmental Organization